THE SUBJECT OF ADMINISTRATIVE LAW: TODAY AND FUTURE - Kunev, Yurii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to form the theoretical foundations of the definition and study of the object and subject of legal regulation of administrative law. Research methods: a comprehensive approach to creating a theoretical picture of the object and subjects and the knowledge that describes and depicts them; comparative legal and doctrinal knowledge of administrative legislation, as well as a method of generalizing and modeling new theoretical knowledge of administrative law. Results: the subjects of administrative law are defined as types of administrative activity. It is substantiated that modern scientific approaches to the study of administrative activity consist in the application of a system-activity methodology, which allows creating reliable models of types of administrative activity and corresponding models of legal norms of administrative legislation. Discussion: the position is argued that the approaches outlined in the article are relevant and promising for solving the main problems of administrative law and legislation and for the development of: scientific research; models of norms of administrative legislation; the system of administrative law; legal regulation of all administrative activity according to the standards of administrative procedure; educational material for textbooks.